Maize Germplasm Characterization and Genetic Approaches for Crop Improvement - El-Esawi, Mohamed (IntechOpen, 2018)
Maize is an important staple food crop worldwide. It is the third most important cereal crop after wheat and rice and is economically used for both livestock feeds and human consumption. The latest maize research has opened up new opportunities for crop improvement. This book brings together recent work and advances that have recently been made in the dynamic fields of genetic characterization, molecular breeding, genetic engineering technologies, and mapping of agronomic traits of global maize germplasm. It also provides new insights into and sheds new light regarding the current research trends and future research directions in maize. This book will provoke interest in many readers, researchers, and scientists, who can find this information useful for the advancement of their research works toward maize improvement.